ИЗУЧЕНИЕ КУЛЬТУРАЛЬНЫХ СВОЙСТВ ВИРУСА ГРИППА ПТИЦ ПОДТИПА Н7N1 НА ЭМБРИОНАХ (Experimental biology, 2015)
Optimal conditions for culturing bird influenza virus in developing chicken embryons were estimated depending on infection dose, incubation time, temperature and age of infected embryon.
Keywords: embryon; virus